2007
DOI: 10.1159/000100078
|View full text |Cite
|
Sign up to set email alerts
|

Maturational Effects of Single and Multiple Early-Life Seizures on AMPA Receptors in Prepubescent Hippocampus

Abstract: The effects of single versus multiple episodes of status epilepticus on the expression of AMPA receptors during a critical growth spurt are unknown. To determine whether the pattern of hippocampal AMPA receptor subunit expression depends upon the age of the animal, timing and number of perinatal seizures, we characterized maturational changes in AMPA receptor protein levels of the hippocampus with immunohistochemistry and Western blotting in rats of juvenile ages with and without a history of neonatal seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 103 publications
3
7
0
Order By: Relevance
“…In line with other studies [32], [38], [44], [49], [50], [51], we found that GluR1, like NR2A, also exhibits expression onset just after the first postnatal week, increases dramatically into adulthood, and is enriched in the PSD at all ages ( Figure 3d : GluR1 comparison by ages: P8, F (2,21)  = 30.729, p <0.0001; P16, F (2,15)  = 6.454, p  = 0.0113; >P40, F (2,17)  = 12.991, p  = 0.0005; GluR1 comparison by fractions: PNS, F (2,17)  = 57.918, p <0.0001; SPM, F (2,17)  = 13.702, p  = 0.0004; PSD, F (2,19)  = 40.306, p <0.0001). The preferential activity-dependent recruitment of GluR1-containing AMPARs is thought to result from LTP during the early phases of synapse maturation [52], [53], [54], [55].…”
Section: Resultssupporting
confidence: 92%
“…In line with other studies [32], [38], [44], [49], [50], [51], we found that GluR1, like NR2A, also exhibits expression onset just after the first postnatal week, increases dramatically into adulthood, and is enriched in the PSD at all ages ( Figure 3d : GluR1 comparison by ages: P8, F (2,21)  = 30.729, p <0.0001; P16, F (2,15)  = 6.454, p  = 0.0113; >P40, F (2,17)  = 12.991, p  = 0.0005; GluR1 comparison by fractions: PNS, F (2,17)  = 57.918, p <0.0001; SPM, F (2,17)  = 13.702, p  = 0.0004; PSD, F (2,19)  = 40.306, p <0.0001). The preferential activity-dependent recruitment of GluR1-containing AMPARs is thought to result from LTP during the early phases of synapse maturation [52], [53], [54], [55].…”
Section: Resultssupporting
confidence: 92%
“…Future studies may reveal the mechanisms involved in mediating this effect on AMPAR-mediated mEPSCs following PTZ-induced seizures, compensatory changes in the excitation-inhibition imbalance may provide information regarding the specific mechanism involved in the paradoxical change observed. Animal models of seizures induced by use of chemoconvulsants in early life have shown multifactorial changes including alterations in the GABARs and AMPARs (Zhang et al, 2004; Silva et al, 2005; Friedman et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In the juvenile period, we previously showed that two early neonatal seizures on P6 and P9 may serve as a preconditioning stimulus by reducing NMDA responses and injury of the CA1 subregion in P20 rats subjected to a third seizure (Liu et al ., ; Friedman et al ., ; Saghyan et al ., ). This study is the first report to examine transcriptomic profiling of the immature hippocampal CA1 with prior early‐life seizure preconditioning.…”
Section: Discussionmentioning
confidence: 99%